PELAKSANAAN REKRUTMEN CALON PEGAWAI NEGERI SIPIL DI LINGKUNGAN KOTA PEKANBARU DENGAN SISTEM COMPUTER ASSISTED TEST (CAT) PADA TAHUN 2014 - Febby Triandini; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Recruitment is one of the management functions of Civil Servants (PNS) are located. Recruitment through an objective, transparent, and accountable expected to obtain human resources (PNS) quality, capable of performing the task in a professional manner. Recruitment Candidates for Civil Servants (CPNS) should have a purpose as the election of the candidates for state officials who have integrity and superior quality, through the recruitment process is transparent and accountable. Society should know the stages in the recruitment process employess using CAT system to avoid errors in execution. The lack of reference books that explain the implementation of the employess with CAT system affecting the smooth implementation of the recruitment procedures that need to be propagated explanation regarding the implementation of the employess with CAT system through the print media. Socialization recruitment procedures to make people understand the CAT system used in the implementation of the civil servant recruitment so that more and more enthusiasts that wish to follow the civil servant recruitment.This study used a qualitative approach. A qualitative approach is an approach used to memproleh information needed in order to learn more on the issues to be discussed in this study. A qualitative approach emphasizes the human element as a research instrument will facilitate the adjustment of the fact that occur in the field. To meet the needs of writing, the authors take the object of this study in Pekanbaru Regional Kepegawain Agency (BKD). Because at the office in charge of the implementation of the civil servant recruitment. The number of informants needed in qualitative research can not be in charge, the research process directly from an information to other information. Selection of informants purposively This meant that informants selected were able to understand and explain it right, giving accurate information on issues of this study. Based on the results of research and discussion, we can conclude that: Implementation of Recruitment employess with System CAT at BKD Kota Pekanbaru hold recruitment include: 1) registration online registration, 2) Filing Requirements, 3) Call Exams and Exam / Test, 4) Announcement of Results Test , Obstacles in the implementation of the civil servant recruitment system BKD CAT in Pekanbaru, among others: a. The factors of the organization, b. Habits of job seekers, c. External factors are derived from the environment.Keywords: Recruitment employess, CAT System